2019
DOI: 10.1101/838474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulsed electric fields create pores in the voltage sensors of voltage-gated ion channels

Abstract: Pulsed electric fields are increasingly used in medicine to transiently increase the cell membrane permeability via electroporation, in order to deliver therapeutic molecules into the cell. One type of events that contributes to this increase in membrane permeability is the formation of pores in the membrane lipid bilayer. However, electrophysiological measurements suggest that membrane proteins are affected as well, particularly voltagegated ion channels (VGICs). The molecular mechanisms by which the electric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…These results suggest that the inhibition and recovery of I Na by twin pulses reflect different processes as they were completely dissociated by MβCD. At longer intervals, twin pulses led to cumulative functional disruption of Na + channels, perhaps by inflicting damage to the channel protein as suggested by the molecular dynamics study by Rems et al [46]. At shorter intervals, we propose that the rapid timing of delivery of the second pulse stimulated the trafficking of newly synthesized and readily assembled Na V subunits from the Golgi and/or endoplasmic reticulum systems toward the membrane.…”
Section: Plos Onementioning
confidence: 54%
See 1 more Smart Citation
“…These results suggest that the inhibition and recovery of I Na by twin pulses reflect different processes as they were completely dissociated by MβCD. At longer intervals, twin pulses led to cumulative functional disruption of Na + channels, perhaps by inflicting damage to the channel protein as suggested by the molecular dynamics study by Rems et al [46]. At shorter intervals, we propose that the rapid timing of delivery of the second pulse stimulated the trafficking of newly synthesized and readily assembled Na V subunits from the Golgi and/or endoplasmic reticulum systems toward the membrane.…”
Section: Plos Onementioning
confidence: 54%
“…Another viable hypothesis to explain the inhibitory effects of NEPs on I Na is that NEPs may directly influence the Na + channel protein. Recent molecular dynamics simulations by Rems et al [46] showed that pulsed electric fields could create alternate conductive pores near the voltage-sensitive domains (VSDs) of voltage-gated ion channels including Na + channels. These alternate pathways were shown to spontaneously evolve into more complex pores stabilized by lipid head groups and were accompanied by unfolding of the VSD from the channel.…”
Section: Plos Onementioning
confidence: 99%